2009
DOI: 10.1158/0008-5472.can-08-2001
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Monitoring of Tumor Response to Chemotherapy by Noninvasive Imaging

Abstract: With the emerging concept of individualized cancer therapy, it becomes crucial to develop methods for the noninvasive assessment of treatment outcome. With this in mind, we designed a novel approach for the comprehensive evaluation of response to chemotherapy with the established agent doxorubicin in a preclinical breast cancer model. This approach delivers information not only about change in tumor size but also about target antigen expression. Our strategy relies on a tumor-specific contrast agent (MN-EPPT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 29 publications
1
80
0
Order By: Relevance
“…In 2006, the same group demonstrated that the dual-modal imaging probe could not only detect orthotopically implanted preclinical models of adenocarcinomas but could also track tumour response to 5-fluorouracil, a clinically used chemotherapeutic agent, in vivo in real time (Medarova et al 2006). More recently, they further proved that tumour delta-T2 was significantly reduced after treatment with DOX drug, indicating a lower accumulation of probe and reflecting the reduced expression of uMUC-1 in orthotopic human breast tumour (Medarova et al 2009). This dual-modality approach delivers information not only about change in tumour size but also about target antigen expression in vivo.…”
Section: Dual-modality Imagingmentioning
confidence: 99%
“…In 2006, the same group demonstrated that the dual-modal imaging probe could not only detect orthotopically implanted preclinical models of adenocarcinomas but could also track tumour response to 5-fluorouracil, a clinically used chemotherapeutic agent, in vivo in real time (Medarova et al 2006). More recently, they further proved that tumour delta-T2 was significantly reduced after treatment with DOX drug, indicating a lower accumulation of probe and reflecting the reduced expression of uMUC-1 in orthotopic human breast tumour (Medarova et al 2009). This dual-modality approach delivers information not only about change in tumour size but also about target antigen expression in vivo.…”
Section: Dual-modality Imagingmentioning
confidence: 99%
“…This would provide direct information on whether the drugs reach their target and on tissue retention time, which would be valuable for the development and evaluation of pharmaceutical products. Third, the presented method can be adapted to study the pharmacokinetics of other contrast agents targeted to, for instance, the Her-2/Neu receptor (27), tumor transglutaminase (28) or the underglycosylated mucin-1 tumor antigen (29). However, differences in extravasation and cellular uptake of probes should be carefully investigated.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Medarova et al [62] have recently designed a particle capable of monitoring a patient's response to chemotherapy with MRI. It is not only tumor size that is monitored but also target antigen expression.…”
Section: Imaging Applications In Common Cancersmentioning
confidence: 99%